2013
DOI: 10.1021/mz400560y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Cyclic Cationic Polymers for Nucleic Acid Delivery

Abstract: The architecture of polycation gene carriers has been shown to affect both their transfection efficiency and cytotoxicity. This work reports the synthesis of cyclic polycations and their use for gene transfer to mammalian cells. Cyclic poly((2-dimethylamino) ethylmethacrylate) (pDMAEMA) homopolymers of various molecular weights were synthesized by "intrachain"click cyclization of α-alkyne-ω-azide heterodifunctional linear precursors prepared by atom transfer radical polymerization (ATRP). Polymers were charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 36 publications
0
66
0
Order By: Relevance
“…First, l ‐alkyne‐PHEMA‐Br was synthesized by ATRP of HEMA in a mixed solvent of isopropyl alcohol (IPA) and DMF . HEMA (1.47 mL, 11.8 mmol), propargyl 2‐bromoisobutyrate (48.3 mg, 0.236 mmol), and bipyridyl (bpy) (73.6 mg, 0.471 mmol) were dissolved in a 9:1% w/w IPA/DMF mixture to obtain a 50% w/w HEMA solution. After three freeze‐pump‐thaw cycles, CuBr (33.9 mg, 0.236 mmol) was then added quickly under the protection of nitrogen flow.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, l ‐alkyne‐PHEMA‐Br was synthesized by ATRP of HEMA in a mixed solvent of isopropyl alcohol (IPA) and DMF . HEMA (1.47 mL, 11.8 mmol), propargyl 2‐bromoisobutyrate (48.3 mg, 0.236 mmol), and bipyridyl (bpy) (73.6 mg, 0.471 mmol) were dissolved in a 9:1% w/w IPA/DMF mixture to obtain a 50% w/w HEMA solution. After three freeze‐pump‐thaw cycles, CuBr (33.9 mg, 0.236 mmol) was then added quickly under the protection of nitrogen flow.…”
Section: Methodsmentioning
confidence: 99%
“…Third, cyclic polymer, c ‐PHEMA, was synthesized by the intrachain click cyclization as reported previously . In a typical procedure, 750 mL of DMF was degassed by nitrogen flow for 1 h at 100 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The expansion of functional ring polymers can not only inspire modeling/simulation studies to reveal the topology effect but also realize the unprecedented functions and properties for their eventual applications. Moreover, the introduction of intelligent segments and moieties can further endow cyclic polymers with on‐demand functions and applications …”
Section: Introductionmentioning
confidence: 99%
“…However, advanced polymeric architectures have been shown in several cases to offer advantages over linear polymers. For example, previous work by Wang et al,[9] Xu et al,[10] Patrickios et al,[11] and our group[12] have revealed the benefits of highly branched, grafted, and cyclic pDMAEMA structures on gene transfer and cell survival compared to linear pDMAEMA structure. Schallon et al also demonstrated that nucleic acid delivery complexes using branched and star pDMAEMA and polyethylenimine polymers traffic differently inside the cell compared to linear polymers, further emphasizing the role of polymeric structure on gene transfer.…”
Section: Introductionmentioning
confidence: 88%
“…ATRP initiator, propargyl 2-bromoisobutyrate (PBrIB) was synthesized as our previous work. [12] Endotoxin-free plasmid pCMV-Luc (Photinuspyralis luciferase under control of the cytomegalovirus (CMV) enhancer/promoter) was produced with the Qiagen Plasmid Giga kit (Qiagen, Hilden, Germany) according to the manufacturer's recommendations. YOYO-1 iodide was purchased from Invitrogen (Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%